Syndromic Surveillance: Developing an early warning system for rabies. Issue 12 (19th December 2022) - ,; Antoniou, Sotiria‐Eleni; Dórea, Fernanda; Dupuy, Céline; Grabowska, Marcelina; Raulo, Saara; Ten Bosch, Quirine; Vial, Flavie; Chuzhakina, Kateryna; Gervelmeyer, Andrea; Aznar, Inma
Abstract: The systematic monitoring of health indicators has the potential to complement conventional (confirmation‐based) surveillance systems, by extracting value from already existing data. A working group (WG) of experts on syndromic and early warning surveillance was formed by EFSA in May 2020 and tasked to develop and test prototype early‐warning animal health surveillance systems covering the wider European region. The first successful pilot of the WG, described in this report, focused on the systematic monitoring of indicators of rabies occurrence. The working assumption of this pilot project is that the number of news articles in media referring to rabies would constitute a good indicator for monitoring sudden changes in occurrence and/or risk of rabies cases in neighbouring EU countries. EFSA, and the European Commission's Joint Research Centre (JRC) worked together on developing a user‐friendly interface for the TIM (Tools for Innovation Monitoring) tool, and particularly the TIM NEWS application. An automatic search (across a predefined number of data sources) for rabies‐related news items was already implemented in the tool. This was used to develop a "dashboard" with spatial and temporal visualisation of the results. This open dashboard will enable authorities involved in rabies risk assessment and management to monitor the daily distribution of media articles related to rabies published worldwide, which is assumed to contribute to disease and risk situation awareness.